Illusory Motion Reversal in Touch - Hsu, Yu-Chun; Yeh, Chun-I; Huang, Jian-Jia; Hung, Chang-Hung; Hung, Chou Po; Pei, Yu-Cheng (Frontiers in Neuroscience, 2019)
Psychophysical visual experiments have shown illusory motion reversal (IMR), in which the perceived direction of motion is the opposite of its actual direction. The tactile form of this illusion has been reported as perceived motion-direction reversal. However, it remains unclear which stimulus characteristics affect the magnitude of IMR. We closely examined the effect of stimulus characteristics on IMR by presenting moving sinusoid gratings and random-dot patterns to subjects’ fingerpads at different spatial periods, speeds, and indentation depths. Most of the recruited subjects perceived motion direction opposite to the veridical direction at least some of the time. The illusion was stronger at spatial periods of 1 and 2 mm and extreme speeds of 20 mm/s and 320 mm/s. We observed stronger IMR for gratings but not the random-dot pattern, indicating that edge orientation might be a major contributor to this illusion. These results show that the optimal parameters for IMR are consistent with the characteristics of motion-selective neurons in the somatosensory cortex, as most of these neurons are also orientation selective. We speculate these neurons could be the neural substrate that accounts for tactile IMR.